2018
DOI: 10.5194/acp-18-3717-2018
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of trace gases from Australian temperate forest fires: emission factors and dependence on modified combustion efficiency

Abstract: Abstract. We characterised trace gas emissions from Australian temperate forest fires through a mixture of open-path Fourier transform infrared (OP-FTIR) measurements and selective ion flow tube mass spectrometry (SIFT-MS) and White cell FTIR analysis of grab samples. We report emission factors for a total of 25 trace gas species measured in smoke from nine prescribed fires. We find significant dependence on modified combustion efficiency (MCE) for some species, although regional differences indicate that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 80 publications
8
26
1
Order By: Relevance
“…Comparing the enhancement ratios estimated here (using the preferred linear regression method) with emission ratios from previous studies of Australian forest fires smoke composition [21,23,29,33] (see Table 5), most enhancement ratios, ER i/CO from this study are between 2 and 3 times lower than emission ratios reported in the literature.…”
Section: Chemical Compositionsupporting
confidence: 37%
See 1 more Smart Citation
“…Comparing the enhancement ratios estimated here (using the preferred linear regression method) with emission ratios from previous studies of Australian forest fires smoke composition [21,23,29,33] (see Table 5), most enhancement ratios, ER i/CO from this study are between 2 and 3 times lower than emission ratios reported in the literature.…”
Section: Chemical Compositionsupporting
confidence: 37%
“…The consequences of inhaled wood-smoke on human health (predominantly on the cardio-vascular system) are well documented in the literature (e.g., References [7][8][9][10][11]). Numerous studies have been undertaken to characterize the chemical composition of smoke from Australian fires ( [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]) and the impacts of these fires on air quality in Australian cities (e.g., References [4,5,10,30]). There have been relatively few studies looking at the composition of wood-smoke pollution from domestic wood heaters in Australia and focus has been predominantly on rural communities, where this source dominates above all others [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to those laboratory studies, a number of field campaigns have also used FTIR spectroscopy to identify trace gases from prescribed fires (Akagi et al, 2013(Akagi et al, , 2014Burling et al, 2011;Goode et al, 2000;Yokelson et al, 1999;Wooster et al, 2011;Alves et al, 2010;Hurst et al, 1994a, b;Paton-Walsh et al, 2008Guérette et al, 2018). Studies that have the ability to measure emissions both near the fire and aloft are especially useful in understanding the complex chemistries that occur during and after prescribed fires, including the (oxidative) chemistry of the downwind plume.…”
Section: Introductionmentioning
confidence: 99%
“…The WASPSS-Auburn campaign incorporated a mobile air quality monitoring station and an open-path infrared Fourier transform spectrometer (OP-FTIR). The OP-FTIR system, which can measure infrared active gases such as CO, NH 3 , N 2 O and CH 4 , has previously been deployed for agricultural [28][29][30] and biomass burning [31,32] emissions estimates. Details of the main findings from the OP-FTIR during WASPSS, which relate to vehicle ammonia emissions and episodes of significant smoke pollution, are presented in two separate papers [33,34].…”
mentioning
confidence: 99%